Creative Works in the 15th Century (When Alisher Navoi Lived) - Toraeva Nilufar Nortoji kizi (Zien Journals, 2023)
In this article, the socio-economic, cultural and educational conditions during the time of Alisher Navoi, the culture and architecture of urban planning during the time of Alisher Navoi, the administration of the country by A. Navoi and Husayn Boykoro, and the creative activities of the country's development ( Buildings and structures built in Herat and its surroundings, in Mashhad, Astrabad, Marv, Mazori Sharif, and other regions of Khorasan, Afghanistan, as well as their architecture, engineering and irrigation facilities), gardens created by A. Navoi and Husayn Boykara and typical of them features are highlighted
Keywords: Social-economic; cultural-educational conditions; urban culture and architecture; administration of Navoi and Huseyn Boykara